1994
DOI: 10.1002/j.1556-6676.1994.tb01732.x
|View full text |Cite
|
Sign up to set email alerts
|

How College Students With and Without Disabilities Perceive Themselves and Each Other

Abstract: This study explored how college students with (n = 80) and without disabilities (n = 76) rated themselves, how each group rated members of the other group, and how each group perceived that the other group would rate them on a 24‐item personality instrument that was designed to assess five factors of personality: extraversion, agreeableness, conscientiousness, emotional stability, and culture. Results revealed that the two groups rated each other in a stereotypical manner: Students with disabilities were seen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
0
7
1
1
Order By: Relevance
“…However, on the college student trait list, negative stereotyping of persons with disabilities was found to occur by students without disabilities and by students with a different disability. Kelly, Sedlacek, and Scales (1994) expanded the Fichten et al (1989)study and found a significant difference in how students with and without disabilities responded to a 24-item personality instrument when comparing how they rated themselves, rated the other group and how they perceived the other group would rate them. The researchers found that students with and without disabilities tended to rate each other in a 'stereotypical manner'.…”
Section: Attitudes Of College Students Towards Persons With Disabilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, on the college student trait list, negative stereotyping of persons with disabilities was found to occur by students without disabilities and by students with a different disability. Kelly, Sedlacek, and Scales (1994) expanded the Fichten et al (1989)study and found a significant difference in how students with and without disabilities responded to a 24-item personality instrument when comparing how they rated themselves, rated the other group and how they perceived the other group would rate them. The researchers found that students with and without disabilities tended to rate each other in a 'stereotypical manner'.…”
Section: Attitudes Of College Students Towards Persons With Disabilitiesmentioning
confidence: 99%
“…In order to meet the needs of the over 60 million individuals with disability in the United States, approximately 21 per cent of the population (Mitka, 1999), a better understanding of attitudes towards persons with disabilities is essential. Specifically, a better understanding of the attitudes of persons without disabilities towards persons with disabilities is required (Kelly, Sedlacek & Scales, 1994). This project was designed to investigate the attitudes of college students, as pre-professionals, towards persons with disabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Turning to the factors potentially underlying recruitment discrimination, one important potential source of discrimination is a stereotyping process by which the mere presence of a facial disfigurement or mobility impairment might cause the perceiver to generate lower impressions of the social and occupational competencies of the applicant (e.g., Heilman, 1983). Several studies have examined how people with disabilities are evaluated in general settings, and a number of consistent factors have emerged (e.g., Bell & Klein, 2001;Fichten & Amsel, 1986;Kelly, Sedlacek, & Scales, 1994;Loo, 2001;Louvet, 2007;Stone & Colella, 1996). People with disabilities are evaluated as being more quiet, shy, unsociable, and lower in interpersonal competence.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have examined how people with disabilities are evaluated in general settings, and a number of consistent factors have emerged (e.g. Bell & Klein, 2001;Fichten & Amsel, 1986;Kelly, Sedlacek & Scales, 1994;Loo, 2001;Louvet, 2007;Stone & Colella, 1996). People with disabilities are evaluated as being more quiet, shy, unsociable, and lower in interpersonal competence.…”
Section: Introductionmentioning
confidence: 99%
“…For example, previous research has documented consistent negative evaluations of people with disabilities (e.g. Bell & Klein, 2001;Fichten & Amsel, 1986;Kelly, Sedlacek & Scales, 1994;Loo, 2001;Louvet, 2007;Stone & Colella, 1996). There is, however, relatively little research systematically documenting how people with facial disfigurement are viewed by the general population.…”
Section: Introductionmentioning
confidence: 99%